1706 Is A "COVID-19-Free" Hospital the Answer to Resuming Elective Surgery During the Current Pandemic? Results from The First Available Prospective Study. (12th October 2021) - Gammeri, E; Cillo, G M; Sunthareswaran, R; Magro, T
Abstract: Background: Resumption of elective surgery during the current coronavirus disease 2019 (COVID-19) pandemic crisis has been debated widely and largely discouraged. This prospective cohort study aimed to assess the feasibility of resuming elective operations during the current and possible future peaks of COVID-19 pandemic. Method: Data were collected during the peak of the first pandemic in the United Kingdom on adult patients who underwent elective surgery in a "COVID-19-free" hospital from April 8 to May 29, 2020. The study included patients from various surgical specialities. Non-elective and pediatric cases were excluded. The primary outcome was 30-day mortality postoperatively. Secondary outcomes were the rate of COVID-19 infections, new onset of pulmonary symptoms after hospitalization and requirement for admission to the intensive care unit. Results: 309 consecutive adult patients were included in this study. No patients died nor required intensive care unit admission. Operations graded "Intermediate" were the most performed procedures. One patient was diagnosed with COVID-19 infection after being transferred to the nearest local emergency hospital for management of postoperative pain and was successfully treated conservatively on the ward. No patient developed pulmonary complications. Three patients were admitted for greater than 23 hours. Twenty-seven patients (8.7%) developed complications. Complications graded as 2 and 3 according to the Clavien-Dindo classification occurred in 14 and 2 patients, respectively. Conclusions: This prospective study shows that, despite the severity and high transmissibility of novel coronavirus 2 diseases, "COVID-19-free" hospitals can represent a safe setting to resume many types of elective surgery during the peak of a pandemic.